Implıcatıons Of The Opening Of Cassation Legal Remedies For PKPU Decisions Due To MK Decısıon Number 23/PUU-XIX/2021 On The Mandate Of The K-PKPU Law - M. Ihsan; Nindyo Pramono; Rio Christiawan; Januar Agung Saputera (Cita Konsultindo Research Center, 2023)
Constitutional Court Decision No. 23/PUU-XIX/2021 opens cassation appeal against PKPU decisions by the Commercial Court in cases filed by creditors and rejected peace offers from debtors. Whereas the non-opening of legal remedies according to Article 235 paragraph (1) and Article 293 paragraph (1) of the K-PKPU Law aims to ensure legal certainty and fulfill the needs of the business world for fair, fast, open, and effective debt settlement. The purpose of this study is to determine the implications of the opening of cassation legal remedies for PKPU decisions due to the Constitutional Court Decision on the mandate of the K-PKPU Law. The method used is normative juridical and qualitative. The results showed that the opening of cassation legal remedies for PKPU decisions due to Constitutional Court Decision No. 23/PUU-XIX/2021 has violated and hampered the mandate of the K-PKPU Law to create legal certainty and resolve debt problems quickly and effectively. That the Constitutional Court's consideration in making Decision No. 23/PUU-XIX/2021 is based on efforts to maintain the realization of justice, however, it must also be understood that the spirit of resolving bankruptcy cases through PKPU is expediency, namely the continuity of the debtor's business. Therefore, it is recommended to regulate the procedure for filing and handling cassation appeals against PKPU decisions with a fast deadline, within which it is still possible to produce quality cassation decisions, and also implement the insolvency test in bankruptcy regulations in Indonesia.